The Performance of Road Transport Infrastructure and its Links to Policies - Braconier, Henrik (OECD Economics Department Working Papers, 2013)
Despite the economic importance of the road transport sector, there is no systematic cross-country evidence on the sector's efficiency. This paper develops a conceptual framework for analysing the social efficiency of the road transport sector, including non-market inputs - such as travel time - and negative outputs - such as accidents and emissions. This framework is then used to analyse efficiency in 32 OECD countries. Data issues in terms of availability, quality and comparability are significant, and the empirical results have to be interpreted with caution. Nevertheless, there is fairly robust evidence that social efficiency is low in a number of OECD countries. The low efficiency suggests that substantial room for input savings exists in these countries. A framework for analysing how road transport policies may impact performance is developed, but a scarcity of data on policy settings currently limits the scope for empirically connecting the two